Muzzle measurements and characteristics of Surti and Jaffarabadi buffalo and its applicability in predicting the age and production performance - SINGH, N P; PATEL, A M (The Indian Journal of Animal Sciences, 2014)
A study was conducted to determine the age and prediction of production performance of buffaloes by a new modified muzzle prints technique. Buffaloes (199) of different age groups and lactating buffaloes (65) belonging to Surti and Jaffarabadi breed were taken. Two types of studies on muzzle, i.e. various muzzle measurements and various muzzles characteristics in sector 2 cm x 2 cm area of the muzzle were carried out. In Surti buffaloes the average basal length, upper length, central length and distance between nostrils were 4.29 ± 0.06,4.01 ± 0.10,4.18 ± 0.15 and 2.25 ± 0.05 cm in 0.0 to 2.9 months age group, while in above 60 months age groups the corresponding values were 8.12 ± 0.13, 7.65± 0.16, 8.31± 0.12 and 4.73 ± 0.06 cm respectively. Similarly in Jaffarabadi, these values were 5.19 ± 0.15, 4.78 ± 0.20, 4.74 ± 0.33 and 2.39 ± 0.10 cm in 0.0 to 5.9 months age group and 9.59 ± 0.14, 9.12 ± 0.29, 9.21 ± 0.16 and 5.33 ± 0.13 cm in above 60 months of age group. The average number of beads varied from 27.11 ± 1.63 to 59.33 ± 1.66 in the age groups of 60 months and above and 6.0 to 11.9 months in Surti and 22.21 ± 2.53 to 63.38 ± 2.86 in the age group of above 60 months and 0.0 to 5.9 months in Jaffarabadi. The total converted beads ranged from a minimum of 45.69 ± 1.38 to a maximum of 100.63 ± 3.95 in Surti, while it was 25.07 ± 3.22 to 96.50 ± 6.60 in laffarabadi buffaloes. Calves had higher number of total converted beads than older ones in both the breeds. The correlation of age with various muzzle measurements were significantly positive (P < 0.01), which indicated the parallel increase in the various muzzle measurements to age of buffaloes, while with muzzle characteristics correlations were negative and significant (P >0.01), which indicated a declined trend with advancement of age. The regression equation showed significant value of R2 to predict the age by various muzzle measurements and various muzzle characteristics i.e. 75.6 % in Surti and 77.6 % in Jaffarabadi. The association of muzzle measurements and characteristics with production traits varied from breed to breed. The regression equations which had more than 60 % R2 values were, Y1 =(-172.48) + 35.66 X and Y2 = (-318.22) + 68.36 XWhere. Y1 = total milk yileld in second month of first lactating Surti buffaloes, Y2 = total milk yield in second and third months of first lactating Surti buffaloes, and X = central length of muzzle of Surti buffaloes.